TET proteins regulate T cell and iNKT cell lineage specification in a TET2 catalytic dependent manner - Äijö, Tarmo; Theofilatos, Dimitris; Cheng, Meng; Smith, Matthew D.; Xiong, Yue; Baldwin, Albert S.; Tsagaratou, Ageliki (Frontiers in Immunology, 2022)
TET proteins mediate DNA demethylation by oxidizing 5-methylcytosine to 5-hydroxymethylcytosine (5hmC) and other oxidative derivatives. We have previously demonstrated a dynamic enrichment of 5hmC during T and invariant natural killer T cell lineage specification. Here, we investigate shared signatures in gene expression of Tet2/3 DKO CD4 single positive (SP) and iNKT cells in the thymus. We discover that TET proteins exert a fundamental role in regulating the expression of the lineage specifying factor Th-POK, which is encoded by Zbtb7b. We demonstrate that TET proteins mediate DNA demethylation, surrounding a proximal enhancer, critical for the intensity of Th-POK expression. In addition, TET proteins drive the DNA demethylation of site A at the Zbtb7b locus to facilitate GATA3 binding. GATA3 induces Th-POK expression in CD4 SP cells. Finally, by introducing a novel mouse model that lacks TET3 and expresses full length, catalytically inactive TET2, we establish a causal link between TET2 catalytic activity and lineage specification of both conventional and unconventional T cells.